Prevention of Low Back Pain - Adinda Putri, Adinda Putri; Haryani, Haryani (International Medical Journal Corp. Ltd, 2024)
Background: The prevention of low back pain (LBP) is a complex issue that necessitates a multifaceted approach, as highlighted by the literature reviewed. The interplay between psychological, physical, and social factors is crucial in understanding LBP and developing effective prevention strategies. (Brandt, 1998) emphasized the significance of psychological evaluations in physical therapy, noting that psychological factors can greatly influence rehabilitation outcomes. Literature Review: Collectively, these articles illustrate the evolving understanding of LBP prevention, emphasizing the necessity of integrating psychological assessments, diverse treatment modalities, and workplace interventions into comprehensive management strategies. The findings underscore the importance of tailored approaches that consider individual patient characteristics, the multifactorial nature of LBP, and the role of education in empowering patients to engage in preventive measures. Conclusion: In conclusion, the prevention of low back pain requires a comprehensive, biopsychosocial approach that integrates psychological evaluations, diverse physical interventions, and workplace modifications. The literature demonstrates that effective prevention strategies must be personalized and adaptable to individual needs, ultimately aiming to improve patient outcomes and reduce the economic burden associated with LBP.